ANTIBIOTIC SENSITIVITY SPECTRUM OF ACUTE BACTERIAL CHOLANGITIS: TRENDS FROM A TERTIARY REFERRAL CENTER IN PAKISTAN - Butt, Muhammad Abdurrahman; Khan, Maahin Manzoor; Omar, Myyra; Atiq, Muslim; Badshah, Maaz; Mohammad Salih,; Rafique, Mehwish; Muhammad Usman,; Kazmi, Syed Murtaza (Journal of Ayub Medical College Abbottabad, 2024)
Background: Significant morbidity can arise from acute bacterial cholangitis. Key to improving outcomes is the implementation of aggressive antibiotic therapy and prompt biliary decompression through either endoscopic or percutaneous means. However, the challenge in treating these infections is amplified by the evolving patterns of antimicrobial resistance, particularly when determining the appropriate empiric therapy. Methods: The present study was conducted at Shifa International Hospital in Islamabad. The patients with the diagnosis of Acute bacterial cholangitis between July 2016 and June 2022 were included. Data was analyzed using SPSS-26.0 to identify any significant associations or correlations among the study variables. Results: A total of 144 patients with a diagnosis of acute bacterial cholangitis were included in the study. 51 of these patients had a positive blood culture. The most commonly identified organism was E. coli, followed by Klebsiella pneumonia, Pseudomonas aeruginosa, Proteus, Enterococcus spp and others. Antibiotic sensitivity pattern revealed resistance to Ceftazidime in 87%, Piperacillin-Tazobactam in 63.7%, Ertapenem in 34.4%, Meropenem in 26.1%, Imipenem in 25.0% and Colistin in 16.1%. Conclusion: A high resistance pattern for antibiotics was observed in our study. This might, in turn, represent the prior judicious use of antibiotics in our community hospitals before these patients are referred to a tertiary referral center.